New La3+ doped TiO2 nanofibers for photocatalytic degradation of organic pollutants: Effects of thermal treatment and doping loadings. Issue 4 (15th February 2022) - Pascariu, Petronela; Cojocaru, Corneliu; Homocianu, Mihaela; Samoila, Petrisor; Dascalu, Andrei; Suchea, Mirela
Abstract: The pure TiO 2 and lanthanum (La 3+ )-doped titanium dioxide (TiO2 ) nanofibers were synthesized by electrospinning method followed via calcination at different temperatures (from 400 °C to 700 °C). Structures of the nanofibers were characterized by X-ray diffraction, scanning electron microscopy, TEM images and diffuse reflectance spectroscopy. The size of the nanofiber diameters was determined to be 129 and 101 nm, for pure TiO 2 and (0.1%)La 3+ :TiO 2 materials, respectively. The prepared nanofibers possess a crystalline structure, and wide distribution of the band-gaps, in the 2.867–3.210 eV range. Effects of La 3+ -dopant content, calcination temperature, and different doses of photocatalysts on the photodegradation efficiency were studied. The optimal level of La 3+ and the optimal temperature of calcination were 0.1% La 3+ and 600 °C, respectively. The photocatalytic degradation of methylene blue (91%, with a rate constant of 2.179 × 10 −2 min −1 ) and ciprofloxacin (CIP) (99.5%, with a rate constant of 1.981 × 10 −2 min −1 ) pollutants was highest on the (0.1%)La 3+ :TiO 2 annealed at 600 °C, after 300 min irradiation under visible light. This photocatalyst displayed sustainable efficiency for CIP degradation up to five consecutive uses.